High Speed Train, New Urban Proximity and Macro-Functional Urban Systems Generation - Fistola, Romano (TeMA - Journal of Land Use, Mobility and Environment, 2008)
The new connections, that high speed railway allows to activate among the metropolitan systems, seem to be able to give life to new urban macro-structures for which the transfer time, among the main poles of the railway segment, it becomes comparable to an inside moving into the city and therefore considered as a interfunctional mobility. The tunnel effect generated by the high speed connection seems to be able to allow a new temporal and functional joint among the metropolitan systems consequently supporting the possibility, for the users, to move themselves among the different urban functions belonging to the different cities. The birth of these urban aggregations seems to conduct toward new megalopolis, which we can define for the first time with the term: joint-city. For this new metropolitan settlement it appears of great interest to investigate the constitutive peculiarities, the systemic articulation, its relationl structures, the evolutionary sceneries, and so on. When new connections are created among functional systems, previously separated, supported by the realization of physical infrastructures (like the HST) it is possible to envisage the birth of new multi-urban organizations, of new macrofunctional urban systems, of joint-cities, whose characteristics and articulations are all to deepen and they offer an interesting mind field to the town planning research.